Urban Food Culture - Leong-Salobir, Cecilia. author. aut Link
VII, 256 p.
Keywords: This book explores the food history of twentieth-century Sydney, Shanghai and Singapore within an Asian Pacific network of flux and flows. It engages with a range of historical perspectives on each city’s food and culinary histories, including colonial culinary legacies, restaurants, cafes, street food, market gardens, supermarkets and cookbooks, examining the exchange of goods and services and how the migration of people to the urban centres informed the social histories of the cities’ foodways in the contexts of culinary nationalism, ethnic identities and globalization. Considering the recent food history of the three cities and its complex narrative of empire, trade networks and migration patterns, this book discusses key aspects of each city’s cuisine in the twentieth century, examining the interwoven threads of colonialism and globalization.